1995
DOI: 10.1074/jbc.270.9.4875
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein K Is a DNA-binding Transactivator

Abstract: We have previously reported that heterogeneous nuclear ribonucleoprotein K (hnRNP K) binds to the pyrimidine-rich strand of the CT element found in the human c-myc gene and activates CT reporter-driven gene expression in vivo. We now characterize the DNA and protein requirements for the interaction of hnRNP K with the CT element. First, hnRNP K is shown to preferentially bind single-stranded DNA over RNA or native double-stranded DNA. Using specific oligoribonucleotide or deoxyribonucleotide probes with specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
171
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 29 publications
7
171
0
Order By: Relevance
“…Then, HMGB1-hnRNP K interaction may connect two systems, which have a large protein-protein interaction potential, in order to extend their respective domains of action even further. For example, hnRNP K was shown to be a transcription-activating factor for the c-myc promoter (43,44). Although we have not been able to establish a direct connection, it is remarkable that c-myc mRNA levels in HMGB1Ϫ/Ϫ mouse cells are about 5-10-fold lower than those in wild type cells.…”
Section: Discussionmentioning
confidence: 99%
“…Then, HMGB1-hnRNP K interaction may connect two systems, which have a large protein-protein interaction potential, in order to extend their respective domains of action even further. For example, hnRNP K was shown to be a transcription-activating factor for the c-myc promoter (43,44). Although we have not been able to establish a direct connection, it is remarkable that c-myc mRNA levels in HMGB1Ϫ/Ϫ mouse cells are about 5-10-fold lower than those in wild type cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a positive control, G/hnRNP K/VP16 was also transfected (21). The hnRNP K protein binds sequence specifically to the top single strand of the PuF site in the c-myc promoter and is able to transactivate PuF/CT containing reporters with or without an artificially attached additional activation domain (21)(22)(23)(24)(25). Two elements of the experimental design are noteworthy.…”
Section: Test For Targeting Of Nm23 To Puf/nhe/ct Elements In Vivo-mentioning
confidence: 99%
“…Despite its function in RNA handling, the precise physiological role of hnRNPs has yet to be fully defined and may include transregulatory effects. Recent studies have shown that the hnRNPs D0B, E2BP, and K are able to bind to double-stranded DNA motifs within the complement receptor 2, hepatitis B virus, and c-myc promoters, respectively (33)(34)(35). hnRNPs can also repress viral DNA replication, repress estrogen-and vitamin D-induced transcription, and transcriptionally regulate various genes, including the rat spi2 gene (30, 36 -38).…”
Section: Discussionmentioning
confidence: 99%